How Do Sustainable Growth Rate Affect Financial Performance of Islamic Banking? Evidence in Southeast Asia Region - Esy Nur Aisyah; Moh. Khoirur Roziqin (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The complexity of banking transactions demands increased competitiveness, efficiency, and risk management. The banking industry needs help in minimizing risk and increasing revenue. ASEAN countries usually measure risk through macro risk measurement, while micro performance contributes to business continuity. Sustainable growth is an essential indicator of company and shareholder performance.Purpose: This study aims to examine the elements that determine the extent of sustainable expansion and their impact on the performance of Islamic banking in Southeast Asia. Design/methodology/approach: The research hypotheses are addressed through the utilization of explanatory research. A purposive sampling method was employed to select 13 Sharia commercial banks for the study, including four from Indonesia, seven from Malaysia, one from Thailand, and one from Brunei Darussalam. The collected data were analyzed using panel data regression. Findings/Result: The study's findings demonstrate that both profit margins and retention levels significantly influence the sustainable growth of Islamic banking in Southeast Asia. Higher profit margins enhance the ability of Islamic banks to generate internal funds, leading to higher rates of sustainable development. Furthermore, an increase in the retained earnings ratio contributes to the bank's capital, while asset turnover does not significantly impact sustainable growth.Conclusion: sustainable growth has a strong positive impact on financial performance, increasing revenue and lowering operating costs, improving financial performance in the region. After increasing revenue, Islamic banking can create Shariah-based products catering to the community's needs. These products must fulfill the principles of ESG (Environmental, Social, Governance) and SDGs (Sustainable Development Goals) to improve sustainability. It will enable future studies to incorporate ESG in assessing sustainable financial performance.Originality/value (State of the art): While SGR's impact on conventional banking has been studied extensively, research focusing on its effects on Islamic banking, particularly in the Southeast Asian context, remains limited. The study aligns with growing global interest in sustainable finance and its role in long-term financial stability, an area Islamic banking inherently emphasizes through ethical investments and risk-sharing. Keywords: retention rate, assets turnover, sustainable growth rate, financial performance, islamic banking